Re-attachment of Subgingivally Oblique Fractured Central Incisor Using a Fiber Post - danir, Necdet; Ok, Evren; Erdek, Yesim (European Journal of Dentistry, 2008)
This case report presents a 32 year old male with an oblique fractured maxillary right central incisor. The procedure used to repair the fracture included flap surgery with an intrasulcular incision and endodontic treatment. The root canal was filled with a root canal sealer and gutta-percha. After root canal obturation, fragments were luted with composite resin using a glass fibers post. After 12 months, clinical and radiographic examinations showed a stable reattachment of the fragments, good aesthetics and periodontal health. (Eur J Dent 2008;2:138-141)
Keywords: Dental trauma; Teeth fractures; Fiber post; Resin composite; Fragment reattachment